High ambipolar and balanced carrier mobility in regioregular poly(3-hexylthiophene) - Choulis, Stelios A.; Kim, Yong Rok; Nelson, Jenny K. (My University, 2004)
The carrier transport of carefully purified regioregular poly(3-hexylthiophene) films has been studied using time-of-flight photocurrent measurements. We find balanced ambipolar transport with a room-temperature mobility for holes of 3×10−4 cm2 V−1 s−1 and for electrons of 1.5×10−4 cm2 V−1 s−1 at electric fields ⩾105 V∕cm. The transport is relatively field independent and weakly temperature dependent, pointing to a high degree of chemical regioregularity and purity. These factors make poly(3-hexylthiophene) attractive for use in a range of electronic applications
Keywords: Electric fields; Ionization; Light emitting diodes; Films